2004
DOI: 10.1128/iai.72.9.4940-4947.2004
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae-Induced Caspase 6-Dependent Apoptosis in Lung Epithelium

Abstract: Streptococcus pneumoniae is the major pathogen of community-acquired pneumonia and one of the most common causes of death due to infectious diseases in industrialized countries. Lung epithelium lines the airways and constitutes the first line of innate defense against respiratory pathogens. Little is known about the molecular interaction of pneumococci with lung epithelial cells. Apoptosis of lung epithelium is involved in some bacterial lung infections. In this study different pneumococcal strains specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 58 publications
(54 reference statements)
1
78
0
Order By: Relevance
“…Here, we observed that S. pneumoniae could cause greater permeability of the cell membrane of host cells (observed as PI uptake), indicative of necrosis. H 2 O 2 may contribute to necrosis, as well as exposure to the pneumococcal cell wall, which has previously been reported to be a necrosis-inducing factor (24,26). With regard to apoptosis, we show that H 2 O 2 secreted by S. pneumoniae leads to DNA damage in a contact-independent fashion and that the levels of H 2 O 2 are sufficiently high to induce significant apoptosis (Annexin V and TUNEL-positive cells).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Here, we observed that S. pneumoniae could cause greater permeability of the cell membrane of host cells (observed as PI uptake), indicative of necrosis. H 2 O 2 may contribute to necrosis, as well as exposure to the pneumococcal cell wall, which has previously been reported to be a necrosis-inducing factor (24,26). With regard to apoptosis, we show that H 2 O 2 secreted by S. pneumoniae leads to DNA damage in a contact-independent fashion and that the levels of H 2 O 2 are sufficiently high to induce significant apoptosis (Annexin V and TUNEL-positive cells).…”
Section: Discussionmentioning
confidence: 71%
“…Another possible source of DNA damage is pneumolysin, a pneumococcal toxin that has been shown to cause apoptosis in alveolar cells when present at high concentrations in cell media in vitro (24). Although pneumolysin is cytoplasmic without any secretory signal (39), others have detected pneumolysin in bacterial supernatant (40,41).…”
Section: S Pneumoniae Induces Dna Damage Responses In Alveolar Epithmentioning
confidence: 99%
See 2 more Smart Citations
“…47 CASP6 is a candidate because it induces apoptosis in response to infection by Streptococous pneumoniae. 48 We sequenced all exons of CASP6, DAPP1, NFkB1, and SCYE1 on genomic DNA, and the cDNA of BANK1 and NFkB1 in at least one CVID patient from the NL1 family. However, no mutations were found in these genes/transcripts.…”
Section: Linkage Of Autosomal-dominant Cv120 To Chromosome 4qmentioning
confidence: 99%